2022
DOI: 10.1124/dmd.122.001037
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Contribution of Each Aldo-Keto Reductase and Short-Chain Dehydrogenase/Reductase Isoform to Reduction Reactions of Compounds Containing a Ketone Group in the Human Liver

Abstract: Enzymes of the aldo-keto reductase (AKR) and short-chain dehydrogenase/reductase superfamilies are involved in the reduction of compounds containing a ketone group. In most cases, multiple isoforms appear to be involved in the reduction of a compound, and the enzyme(s) that are responsible for the reaction in the human liver have not been elucidated.The purpose of this study was to quantitatively evaluate the contribution of each isoform to reduction reactions in the human liver. Recombinant cytosolic isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…CBR1 catalyzes the reduction reaction of several drugs, such as loxoprofen and haloperidol (Ohara et al, 1995;Kudo and Ishizaki, 1999). Recently, we found that the contributions of CBR1, AKR1C3, and AKR1C4 to loxoprofen reduction in human liver cytosol were 31%, 54%, and 34%, respectively (Ichida et al, 2023a). When we evaluated CBR1 and AKR1C3 protein levels by immunoblotting, their levels were higher in the intestine than in the liver.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…CBR1 catalyzes the reduction reaction of several drugs, such as loxoprofen and haloperidol (Ohara et al, 1995;Kudo and Ishizaki, 1999). Recently, we found that the contributions of CBR1, AKR1C3, and AKR1C4 to loxoprofen reduction in human liver cytosol were 31%, 54%, and 34%, respectively (Ichida et al, 2023a). When we evaluated CBR1 and AKR1C3 protein levels by immunoblotting, their levels were higher in the intestine than in the liver.…”
Section: Discussionmentioning
confidence: 88%
“…In support of this, loxoprofen reductase activity in human intestinal cytosol was 4.5-fold higher than that in human liver cytosol (151 ± 2.1 pmol/min/mg protein vs 35.8 ± 1.4 pmol/min/mg protein) at a substrate concentration of 5 µM (Suzuki et al, in preparation). It has been reported that the CL int value of the reduction reaction for haloperidol, which is a substrate specific for CBR1 (Ichida et al, 2023a), in the human intestinal cytosol (0.016 mL/min/mg protein) is 2.7-fold higher than that in the human liver cytosol (0.006 mL/min/mg protein) (Nishimuta et al, 2013). Thus, the reduction reaction of CBR1 substrates would occur substantially in the intestine in addition to the liver.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among them, 12 isoforms, AKR1A1, 1B1, 1B10, 1B15, 1C1, 1C2, 1C3, 1C4, 1D1, 1E2, 7A2, and 7A3, have been reported to be involved in the reduction reaction of xenobiotics (Fukami et al, 2022). The human SDR family consists of 75 isoforms (Persson and Kallberg, 2013), and 7 isoforms, carbonyl reductase (CBR) 1, 3, 4, 11β-hydroxysteroid dehydrogenase type 1 (HSD11B1), 17β-hydroxysteroid dehydrogenase type 12 (HSD17B12), dehydrogenase/reductase member (DHRS) 4, and dicarbonyl/ L -xylulose reductase (DCXR), have been suggested to be involved in the reduction reaction of xenobiotics (Matsunaga et al, 2006, Ichida et al, 2023a. Among these members, AKR1C1, AKR1C2, AKR1C3, AKR1C4, CBR1, and HSD11B1 are highly expressed in the liver and contribute to the reduction reaction of clinically used drugs (Barski et al, 2008;Amai et al, 2020) with overlapping substrate specificities (Ichida et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%